Children’s Mental Health During the First Two Years of the COVID-19 Pandemic: Burden, Risk Factors and Posttraumatic Growth – A Mixed-Methods Parents’ Perspective - Wenter, Anna; Schickl, Maximilian; Sevecke, Kathrin; Juen, Barbara; Exenberger, Silvia (Frontiers in Psychology, 2022)
The COVID-19 pandemic and the accompanying containment measures such as physical distancing and school closures led to major changes in children’s everyday lives. By means of a mixed-methods study, the “Tyrolean COVID-19 Children’s Study” investigated the effects of the pandemic and factors influencing mental health and health-related quality of life of North Tyrolean (Austria) and South Tyrolean (Italy) children aged 3–13 years. Parents filled out N = 2,691 online questionnaires (951 preschool children: 3–6 years; 1,740 schoolchildren: 7–13 years) at four measurement time points (March 2020, December 2020, June 2021, December 2021). For both age groups, children’s mental health outcomes (internalising problems, posttraumatic stress symptoms) were worse in December 2021 (t4) than children’s mental health outcomes in March 2020 (t1). With regard to aggressive behaviour, this difference was only found among schoolchildren. Thematic analysis of an open ended, written question revealed the following positive changes in children during the Corona crisis: (1) the importance of intra- and extra-familial relationships, (2) new competences and experiences, (3) values and virtues, (4) use of time, and (5) family strength. Using multilevel modelling, threat experience, economic disruption, and perceived posttraumatic growth were shown to be the strongest predictors of all outcomes. Additionally, male gender was shown to be a predictor of aggressive behaviour. In terms of age, schoolchildren showed more internalising problems, aggressive behaviour, and threat experience than preschool children. With regard to time, parents in December 2021 reported more threat experience in older children and less perceived posttraumatic growth in both older and younger children, than parents at the beginning of the pandemic. Targeted support for vulnerable children may prevent longer-term development of psychopathologies and contribute to society’s psychosocial resilience in the current COVID-19 pandemic. Moreover, sustainable promotion of children’s posttraumatic growth can also contribute to children’s mental health and could even offer a chance to turn the crisis into an opportunity.